Diabetic autonomic neuropathy and iritis: an association suggesting an immunological cause. Issue 6441 (11th August 1984) - Guy, R J; Richards, F; Edmonds, M E; Watkins, P J
Abstract : Of 47 insulin requiring diabetics aged 21-40 years with autonomic neuropathy (heart rate variability less than 10), 14 had previously developed iritis. In all except two cases the iritis preceded the autonomic symptoms. The autonomic neuropathy was very severe, 10 patients having two or more characteristic symptoms. Ten of the patients with iritis were women. The association of iritis (itself an immune disorder) with severe symptomatic autonomic neuropathy raises the possibility of an underlying immunological basis for autonomic neuropathy.